Colloidal nanocomposite of TiN and N-doped few-layer graphene for plasmonics and electrocatalysis - Shanker, G. Shiva; Markad, Ganesh B.; Jagadeeswararao, Metikoti; Bansode, Umesh; Nag, Angshuman (ACS Energy Letters, 2017)
A combination of high carrier density, high surface area, solution processability, and low cost is desired in a material for electrocatalytic applications, including H-2 evolution and a counter electrode of a solar cell. Also, plasmonic-based applications in biological systems can be derived from such material. In this regard, a colloidal nanocomposite of TiN and N-doped few-layer graphene (TiN NFG) is synthesized from molecular precursors. TiN nano crystals (NCs) provide free electrons for electrical conductivity and plasmonics, whereas NFG is responsible for charge transport, high surface area, and colloidal stability. Colloidal TiN NFG nano composites exhibit a localized surface plasmon resonance band at around 700 nm. Coatings of the nanocomposite form a counter electrode for efficient (8.9%) dye-sensitized solar cells. Furthermore, the nanocomposite acts as an efficient electrocatalyst for hydrogen evolution reaction, exhibiting an overpotential similar to 161 mV at a current density of 10 mA/cm(2).